Fiscal policy ciclicity - Koliesnichenko, Anastasiia (Дніпровський державний університет внутрішніх справ, 2024)
The enterprise’s activity is formed taking into account exogenous processes, due to the single or multiplicative influence of a number of factors of different nature in terms of the nature of the impact, predictability, the model of the enterprise’s response, the consequences of the impact, the level of controllability. The factor of cyclical economic development has a special influence on the operation of the enterprise. Certain elements may also be subject to cyclical effects, in particular: the product, the enterprise itself, the industry, the region or the national economy. The study of the impact of the cyclical development of the economy on the activities of modern enterprises is an important scientific and practical task, the solution of which in the conditions of modern economic realities acquires unconditional relevance. Purpose of the article is to investigate the peculiarities of the formation of the financial policy of the state in the conditions of cyclical economic development; conduct an analysis of the components that determine the nature of the fiscal impulse; determine the key aspects of building an effective fiscal policy, taking into account cyclical fluctuations. General scientific and special methods are used: analysis, synthesis, tabular-graphic, theoretical generalization and abstract-logical. The conducted research made it possible to obtain a comprehensive understanding of the peculiarities of the formation of the financial policy of the state in the conditions of cyclical development of the economy. It is determined that cyclical processes affect the contour and strength of the fiscal impulse, which forces enterprises and organizations to adapt by systematizing, evaluating and analyzing the changes that occur. An assessment of the financial policy was carried out from the point of view of cyclical and structural components can be characterized, as a result of which it was justified that the cyclical and structural components of fiscal policy determine a number of processes related to the budgeting of state revenues and expenses. It is proven that public finances, the stability of which functionally affects the flexibility of fiscal rules and norms, are prone to long-term economic shocks, which as a result distorts the symmetry of reactions to structural and cyclical changes in the mechanism of fiscal consolidation. The practical value of the conducted research lies in the implementation of effective fiscal policy, which allows to ensure its main goals, in particular: smoothing cyclical fluctuations of the economy, promotion of sustainable economic growth, moderate rates of inflation. The key to the reproduction of a balanced fiscal policy in the medium and long term is the adoption of a complex of fiscal rules, which should be effective taking into account external factors and the macroeconomic situation in the country.

Діяльність підприємства формується з врахуванням екзогенних процесів, через поодинокий або ультиплікативний вплив низки чинників, що мають різну природу за характером впливу, прогнозованістю, моделлю реакції підприємства, наслідками впливу, рівнем контрольованості. Особливий вплив на функціонування підприємства здійснює фактор циклічності економічного розвитку. Циклічним впливам також можуть бути схильні окремі елементи, зокрема: товар, саме підприємство, галузь, регіон або національна економіка. Дослідження впливу циклічного розвитку економіки на діяльність сучасних підприємств є важливим науково-практичним завданням, вирішення якого в умовах сучасних економічних реалій набуває безумовної актуальності. Мета статті – дослідити особливості формування фінансової політики держави в умовах циклічного розвитку економіки; провести аналіз компонент, які визначають характер фіскального імпульсу; визначити ключові аспекти побудови ефективної фіскальної політики з врахуванням циклічних коливань. Використано загальнонаукові та спеціальні методи: аналізу, синтезу, таблично-графічний, теоретичного узагальнення та абстрактно-логічний. Проведені дослідження дозволили отримати комплексне уявлення щодо особливостей формування фінансової політики держави в умовах циклічного розвитку економіки. Визначено, що циклічні процеси впливають на контур та потужність фіскального імпульсу, що змушує підприємства та організації адаптуватися шляхом систематизації, оцінки та аналізу змін, які відбуваються. Було проведено оцінку фінансової політики з позиції циклічної та структурної компонент можна охарактеризувати, в результаті чого було обґрунтовано, що циклічна та структурна компоненти фіскальної політики обумовлюють ряд процесів, пов’язаних з бюджетуванням державних доходів і витрат. Доведено, що державні фінанси, стійкість яких функціонально впливає на гнучкість фіскальних правил і норм, є схильними до тривалих економічних шоків, що в результаті викривляє симетричність реакцій на структурні та циклічні зміни у механізмі фіскальної консолідації. Практична цінність проведеного дослідження полягає у реалізації ефективної фіскальної політики, яка дозволяє забезпечити її основні цілі, зокрема: згладжування циклічних коливань економіки, сприяння стійкому економічному зростанню, помірні темпи інфляції. Ключем у відтворенні збалансованої фіскальної політики у середньо- й довгостроковій перспективах виступає прийняття комплексу фіскальних правил, які мають бути дієвими з врахуванням зовнішніх факторів та макроекономічної ситуації в країні.
Циклічність фіскальної політики
Keywords: fiscal policy; cyclical fluctuations; fiscal consolidation; iscal impulse; budget and tax institutions; фіскальна політика; циклічні коливання; фіскальна консолідація; фіскальний імпульс; бюджетно-податкові інститути